Antibiotics prescription for targeted therapy of pediatric invasive pneumococcal diseases in China: a multicenter retrospective study - Tian-ming Chen (BMC, 2021)
Abstract Background Streptococcus pneumoniae (S. pneumoniae) is a major cause of bacterial meningitis, septicemia and pneumonia in children. Inappropriate choice of antibiotic can have important adverse consequences for both the individual and the community. Here, we focused on penicillin/cefotaxime non-susceptibility of S. pneumoniae and evaluated appropriateness of targeted antibiotic therapy for children with IPD (invasive pneumococcal diseases) in China. Methods A multicenter retrospective study was conducted in 14 hospitals from 13 provinces in China. Antibiotics prescription, clinical features and resistance patterns of IPD cases from January 2012 to December 2017 were collected. Appropriateness of targeted antibiotics therapy was assessed. Results 806 IPD cases were collected. The non-susceptibility rates of S. pneumoniae to penicillin and cefotaxime were 40.9% and 20.7% respectively in 492 non-meningitis cases, whereas those were 73.2% and 43.0% respectively in 314 meningitis cases. Carbapenems were used in 21.3% of non-meningitis cases and 42.0% of meningitis cases for targeted therapy. For 390 non-meningitis cases with isolates susceptible to cefotaxime, vancomycin and linezolid were used in 17.9% and 8.7% of cases respectively for targeted therapy. For 179 meningitis cases with isolates susceptible to cefotaxime, vancomycin and linezolid were prescribed in 55.3% and 15.6% of cases respectively. Overall, inappropriate targeted therapies were identified in 361 (44.8%) of 806 IPD cases, including 232 (28.8%) cases with inappropriate use of carbapenems, 169 (21.0%) cases with inappropriate use of vancomycin and 62 (7.7%) cases with inappropriate use of linezolid. Conclusions Antibiotic regimens for IPD definite therapy were often excessive with extensive prescription of carbapenems, vancomycin or linezolid in China. Antimicrobial stewardship programs should be implemented to improve antimicrobial use.